Answer:
Endpoint at one end and an arrow at the other end.
Step-by-step explanation:
Answer:
12
Step-by-step explanation:
Answer:
9
Step-by-step explanation:
In this item we are given with the equation, 2x - y = 3. The equation contains two variables, x and y. We assume in this item that the value of x is independent of the value of y; however, y values depends on the given values of x. In parametric form, the equation would take the form,
f(x) = y = ax + b
where a is the numerical coefficient of x and b is constant. Transforming the given equation to this form,
f(x) = y = 2x - 3